Nitrofurantoin resistance mechanism and fitness cost in Escherichia coli - Sandegren, Linus; Lindqvist, Anton; Kahlmeter, Gunnar; Andersson, Dan I (Journal of antimicrobial chemotherapy, 2008)
The biological fitness cost of antibiotic resistance is a key parameter in determining the rate of appearance and spread of antibiotic-resistant bacteria. We identified mutations conferring nitrofurantoin resistance and examined their effect on the fitness of clinical Escherichia coli isolates. By plating bacterial cells on agar plates containing nitrofurantoin, spontaneous nitrofurantoin-resistant E. coli mutants were isolated. The fitness of susceptible and resistant strains was measured as growth rate in the presence and absence of nitrofurantoin in rich culture medium. Time-kill kinetics of the resistant mutants was compared with the susceptible strains. Resistance mutations were identified by DNA sequencing. Spontaneous resistant mutants of initially susceptible clinical E. coli appeared with a rate of 10(-7)/cell/generation, and these mutants showed a reduction in the growth rate compared with the susceptible parent strain. Similarly, comparison of a set of susceptible and resistant clinical isolates of E. coli showed that the average growth rate of the resistant mutants was approximately 6% lower than the susceptible strains. Furthermore, the bacterial growth rate in the presence of nitrofurantoin at therapeutic levels was greatly reduced even for nitrofurantoin-resistant mutants. The resistance-conferring mutations were identified in the nsfA and nfsB genes that encode oxygen-insensitive nitroreductases. Nitrofurantoin resistance confers a reduction in fitness in E. coli in the absence of antibiotic. In the presence of therapeutic levels of nitrofurantoin, even resistant mutants are so disturbed in growth that they are probably unable to become enriched and establish an infection.